2020
DOI: 10.1590/0103-6440202003328
|View full text |Cite
|
Sign up to set email alerts
|

Filling Ability and Flow of Root Canal Sealers: A Micro-Computed Tomographic Study

Abstract: This study evaluated by micro-computed tomography (μCT) the filling ability in curved root canals, besides the flow of AH Plus (AHP) and Neo MTA Plus (NMTAP) sealers using different methodologies. Mandibular molars mesial roots with two root canals and degree of curvature between 20° and 40° were selected. The specimens were prepared with the ProDesign R system up to size 35.05 and were filled with the sealers by a continuous wave of condensation technique, Thermo Pack II (n=12). The teeth were scanned using μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
(38 reference statements)
0
7
0
Order By: Relevance
“… 23 Therefore, the apical enlargement allows greater contact of the instrument and dentin walls reducing debris, providing better effect of the irrigating solution 24 and root canal filling. 25 In addition, the decrease of residual filling material was observed after apical enlargement from size 25 to 40, 26 with a success rate of 90.4% after 2 years. 27 Although our study showed a percentage of remaining material less than 20% in the apical third after apical enlargement, the complete removal of filling material was not possible.…”
Section: Discussionmentioning
confidence: 88%
“… 23 Therefore, the apical enlargement allows greater contact of the instrument and dentin walls reducing debris, providing better effect of the irrigating solution 24 and root canal filling. 25 In addition, the decrease of residual filling material was observed after apical enlargement from size 25 to 40, 26 with a success rate of 90.4% after 2 years. 27 Although our study showed a percentage of remaining material less than 20% in the apical third after apical enlargement, the complete removal of filling material was not possible.…”
Section: Discussionmentioning
confidence: 88%
“…Sci. 2024, 14, 480 2 of 14 system, preventing both bacterial colonization and the infiltration of oral cavity fluids into periapical tissues and thus establishing suitable conditions for periradicular tissue healing [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Proper filling of the root canal system is a key factor in achieving higher rates of endodontic treatment success 1 . Voids in the filling provide a greater chance for reinfection 2 , 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, different obturation techniques have been proposed to optimize root canal filling 3 . The use of an endodontic sealer is essential to fill the spaces between gutta-percha and root canal walls, as well as areas of anatomical complexities, such as curvatures and lateral canals 1 , 2 , 3 . Endodontic sealers must have adequate flow, aiming to fill irregularities in the root canal system 1 .…”
Section: Introductionmentioning
confidence: 99%